Looking for Alaska - Green, John. (New York : Speak, 2007)
Sixteen-year-old Miles' first year at Culver Creek Preparatory School in Alabama includes good friends and great pranks, but is defined by the search for answers about life and death after a fatal car crash.
Young Adult
Young Adult.
Wilson's Senior High School
School Library Journal starred
Five Owls
930
Keywords: Interpersonal relations -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Death -- Fiction; Interpersonal relations -- Fiction; Private schools -- Fiction; School stories; Death -- Fiction